Social isolation and its relationship to multidimensional poverty - Samuel, K; Alkire, S; Zavaleta, D; Mills, C; Hammock, J (Routledge, 2018)
While the multidimensionality of poverty is well-recognised, one dimension of poverty which has been often overlooked is weak social connectedness. This paper draws on conceptual, participatory and measurement literatures to show that social connectedness appears to be an important missing ingredient of multidimensional poverty analyses, with social isolation being a feature which exacerbates the condition of poor persons. To provide contextual detail as to its impact on persons in marginalized communities, we present qualitative primary data from South Africa and Mozambique and review pertinent studies of the First Nations of Canada and among persons with disability. A policy challenge for social isolation is that it is often seen as stemming from an individuals’ capacity rather than resulting from the broader social context. The closing section outlines areas for policy.